Training Pharmacy Students in Self-Medication Counseling Using an Objective Structured Clinical Examination–Based Approach. (May 2021) - Farahani, Imaneh; Farahani, Samieh; Deters, Maira Anna; Schwender, Holger; Laeer, Stephanie
Introduction: Pharmacists play an important role in ensuring the safe, effective, and rational use of drugs in self-medication. Given the potential risks of self-medication, adequate training on self-medication counseling should be provided to pharmacy students during their academic education. Objective structured clinical examinations (OSCEs) could be used to train pharmacy students in these skills. This study evaluated the efficacy of an OSCE-based approach for training pharmacy students in self-medication counseling and communication skills. Methods: This randomized controlled study was conducted among pharmacy students using a pre-post design. The intervention group completed OSCE-based self-medication training, while the control group collected counseling-relevant information from summaries of product characteristics of over-the-counter drugs. The counseling and communication skills of both groups before and after training were assessed by completing OSCEs. The participants completed a self-assessment questionnaire on self-confidence and self-perceived proficiency before each OSCE encounter and a satisfaction survey at the end of the seminar. Results: Students were generally satisfied with the seminar. While the OSCE-trained group demonstrated significantly greater increases in counseling skills and self-confidence and self-perceived proficiency than the control group, both groups had similar increases in communication skills. Conclusion: The present study suggests that applying OSCEs as a learning tool for self-medication counseling is beneficial for improving students' counseling skills as well as self-confidence and self-perceived proficiency. These results support the inclusion of OSCEs in pharmacy education and highlight its potential to bridge gaps between knowledge and practice.